Socialization Making Media Learning Interactive E-Module based Flippbook in Elementary School 4 Maiwa - Hermansyah, Sam; Nasmilah, Nasmilah; Pammu, Abidin; Saleh, Noer Jihad; Huazheng, Han; Congzhao, Huang (Yayasan Pendidikan Islam Daarut Thufulah, 2023)
The learning process will be more effective if it uses many learning resources, one of which is a module. For efficiency, modules can be packaged into a digital form called e-module based philipbook. From facet access And convenience in bring, e-module Can accessed And opened anywhere is at. On study This done socialization making media e-module based flipbook to elementary school teachers through stages planning, implementation, And taking questionnaire data follow-up after training. Results media implementation based E-Module learning Flipbooks teachers can develop Flipbook-based E-Module learning media so that the process teaching and learning between educators and students becomes more optimal and fun as well increase enthusiastic And Spirit in learning.